ChemInform Abstract: The Use of Silyl Ketene Acetals and Enol Ethers in the Catalytic Enantioselective Alkylative Ring Opening of Oxa/Aza Bicyclic Alkenes. Issue 48 (2nd December 2014) - Zhang, Lei; Le, Christine M.; Lautens, Mark
Abstract Several further transformations of the primary reaction products are described.